2020
DOI: 10.1371/journal.pone.0233011
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of Hippophae rhamnoides shrub in response of sea-level rise and insect outbreaks

Abstract: The coastal vegetation of islands is expected to be affected by future sea-level rise and other anthropogenic impacts. The biodiverse coastal vegetation on the eastern part of the Dutch Wadden Island of Ameland has experienced land subsidence caused by gas extraction since 1986. This subsidence mimics future sea-level rising through increased flooding and raising groundwater levels. We studied the effects of this relative sea-level rise and other environmental factors (i.e. insect outbreaks, temperature and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…After 1990, large parts of the Hippophae shrubland collapsed and returned to grasslands. This is due to the lifespan of Hippophae of around 40 years, which equals the timespan between the 1954 outbreak of myxomatosis and1990 (Van der Hagen et al 2020b) but note that the lifespan of Hippophae can vary between 18 and 56 years, incidentally up to 80 years (Zoon 1995;Provoost and Declerck 2020;Decuyper et al 2020). However, our permanent plot data showed that shrubland shifted mainly into tall shrubs (e.g., Crataegus monogyna; Van der Hagen 2020b) from 1972 to 2012 (Fig.…”
Section: The Role Of Rabbits In Dune Grasslands Conservationmentioning
confidence: 99%
“…After 1990, large parts of the Hippophae shrubland collapsed and returned to grasslands. This is due to the lifespan of Hippophae of around 40 years, which equals the timespan between the 1954 outbreak of myxomatosis and1990 (Van der Hagen et al 2020b) but note that the lifespan of Hippophae can vary between 18 and 56 years, incidentally up to 80 years (Zoon 1995;Provoost and Declerck 2020;Decuyper et al 2020). However, our permanent plot data showed that shrubland shifted mainly into tall shrubs (e.g., Crataegus monogyna; Van der Hagen 2020b) from 1972 to 2012 (Fig.…”
Section: The Role Of Rabbits In Dune Grasslands Conservationmentioning
confidence: 99%